Chapter Environmental training of the Italian Coast Guard between tradition and innovation - Altavilla, Santo (Proceedings e report, 2020)
The Coast Guard is an organization committed to safeguarding the marine environment, that requires specialized personnel. Therefore, it is necessary to integrate the "basic" preparation, with "specialist" training in compliance with the high standards of a Q.M.S. of training, which uses teaching methods advanced, classroom and lessons, case studies, but also practice in the field. The latter methodology plays an important role since learning by doing, even more than theory, guarantees the effectiveness of learning, emotional involvement and the formation of experiential memory of learners.